The digitization of healthcare : new challenges and opportunities - Menvielle, Loick; Audrain, Anne-Françoise; Menvielle, William (Palgrave Macmillan, 2017)
Combining conceptual, pragmatic and operational approaches, this edited collection addresses the demand for knowledge and understanding of IT in the healthcare sector. With new technology outbreaks, our vision of healthcare has been drastically changed, switching from a 'traditional' path to a digitalized one. Providing an overview of the role of IT in the healthcare sector, The Digitization of Healthcare illustrates the potential benefits and challenges for all those involved in delivering care to the patient. The incursion of IT has disrupted the value chain and changed business models for companies working in the health sector, and also raised ethical issues and new paradigms about delivering care. This book illustrates the rise of patient empowerment through the development of patient communities such as PatientLikeMe, and medical collaborate platforms such as DockCheck, thus providing a necessary tool to patients, caregivers and academics alike.